Magnetic resonance imaging volumetric analysis for diabetic striatopathy with two episodes of hemichorea-hemiballism syndrome: A case report. Issue 38 (September 2019) - Lin, Yi-Te; Chen, Shih-Chung; Yip, Ping-Keung; Wang, Vinchi
Abstract: Rationale: Diabetic striatopathy (DS) is an uncommon movement disorder among diabetic patients characterized by clinical hemichorea-hemiballism with neuroimage change of the striatum. Here, we report a case of DS with relapsed hemichorea-hemiballism attacks even during euglycemic period, and the MRI changes by volumetric analysis. Patient concerns: A 69-year-old diabetic female suffered from a relapsed episode of hemichorea-hemiballism during her euglycemic period after the treatment of hyperglycemia. Diagnoses: To investigate the serial MRI changes in a case with diabetic striatopathy who had clinical hemichorea-hemiballism syndrome. Interventions: Semi-quantitative volumetric analyses from T1 images of these brain MRIs were obtained during the disease course. Outcomes: Besides, the negative finding of the first brain MRI during her first hospital admission, three afterward MRI examinations disclosed a waxing-and-waning mode of volume change from high-signal T1 images in left striatum. The clinical symptoms paralleled with the neuroimage changes in striatum. The MR signal volume changes were valuable for the clinical course of the hemichorea-hemiballism caused by diabetic striatopathy Lessons: Serial MR images for the diabetic striatopathy presented as a key pathognomonic relationship with the clinical hemichorea-hemiballism syndrome, assessed by our simplied volumetric analysis. Clinical involuntary movements may relapse and persist even with euglycemic condition as our case.